HUBUNGAN STATUS GIZI DENGAN STRESS KECEMASAN DAN DEPRESI PADA ANAK SEKOLAH DASAR: THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND STRESS, ANXIETY AND DEPRESSION IN ELEMENTARY SCHOOL CHILDREN - Brigitte Sarah Renyoet; Dary Dary; Lady Triwulandari (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2026)
Introduction: Stress, anxiety, and depression can be experienced by all age groups, including elementary school children. These conditions have the potential to affect eating behavior and impact children's nutritional status. Objective: This study aims to analyze the relationship between stress, anxiety, and depression and nutritional status in students at Eben Haezer Christian Elementary School 03 in Salatiga. This study used a quantitative approach with a cross-sectional design on children aged 10-12 years. Data collection was conducted through anthropometric measurements (BMI/U), Food Frequency Questionnaire (FFQ) interviews, 2x24-hour recall, and Depression Anxiety Stress Scales (DASS) questionnaires. The study was conducted from January to March 2025. Results: The results showed that most respondents had good nutritional status, with 10% underweight and 21.8% overweight. Individuals showed symptoms of mild stress in 51.8% of children, normal anxiety symptoms in 28.1%, and moderate depression symptoms in 58.1%. The chi-square test showed no significant relationship between nutritional status and stress, anxiety, or depression (p>0.05). Conclusion: In conclusion, psychological factors such as stress, anxiety, and depression do not directly affect children's nutritional status, but may play a role through changes in eating behavior and physical activity. Keyword : depression, anxiety, nutritional status, stres